Influence of Age Combination and Protein Supplementation on the Rate of Lay, Egg Quality and Chick Viability - Ylagan, Arthur (Romblon State University Research Journal, 2014)
Farm trail was conducted to determine the effect of short-term game fowl management interventions on egg production and chick viability. It involved two studies. In study 1, the experimental treatments were: a) brood cock x brood pullets, b) brood stag x brood hens, c) brood cock x brood hens, and d) brood stag x brood pullets. In Study 2, protein supplementation at different day intervals with different dosage (number of capsule) were used: a) zero supplementation, b) one capsule per week, c) two capsules per week, and d) three capsules per week. Results showed that egg production, egg shape index, hatchability and chick viability were not influenced by age combination of brood fowls. with high protein concentrate and energy utilization enhancer did not influence egg production and egg and chick viability. There were relative improvements in egg and chick viability, suggesring that those may be with long term supplementation. It is recommended that a study for longer duration of time of pairing of different combinations be conducted to further test the productive efficiency in terms of rate of lay, hatchability and chick viability, and supplementing brood fowl with energy utilization enhancer for a longer duration of time and with a bigger experimental bird population.